Skeletal muscle morphology in sarcopenia defined using the EWGSOP criteria: findings from the Hertfordshire Sarcopenia Study (HSS) - Patel, H. P. (BMC Geriatr, 2015)
BACKGROUND: Sarcopenia is defined as the loss of muscle mass and function with age and is associated with decline in mobility, frailty, falls and mortality. There is considerable interest in understanding the underlying mechanisms. Our aim was to characterise muscle morphology changes associated with sarcopenia among community dwelling older men. METHODS: One hundred and five men aged 68–76 years were recruited to the Hertfordshire Sarcopenia Study (HSS) for detailed characterisation of muscle including measures of muscle mass, strength and function. Muscle tissue was obtained from a biopsy of the vastus lateralis for 99 men and was processed for immunohistochemical studies to determine myofibre distribution and area, capillarisation and satellite cell (SC) density. RESULTS: Six (6 %) men had sarcopenia as defined by the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. These men had lower SC density (1.7 cells/mm(2) vs 3.8 cells/mm(2), p = 0.06) and lower SC/fibre ratio (0.02 vs 0.06, p = 0.06) than men without sarcopenia. Although men with sarcopenia tended to have smaller myofibres and lower capillary to fibre ratio, these relationships were not statistically significant. CONCLUSION: We have shown that there may be altered muscle morphology parameters in older men with sarcopenia. These results have the potential to help identify cell and molecular targets for therapeutic intervention. This work now requires extension to larger studies which also include women.